The relevance of anti-pf4 antibody isotypes and endogenous glycosaminoglycans and their relationship with inflammatory biomarkers in pulmonary embolism patients - Kantarcioglu, Bulent; Darki, Amir; Siddiqui, Fakiha; Hoppensteadt, Debra; Lewis, Joseph; Krämer, Roland; Adiguzel, Cafer; Fareed, Jawed (Clinical and applied thrombosis, hemostasis, 2022)
IntroductionPrevious studies have shown that inflammation may contribute to the interplay of endogenous glycosaminoglycans (GAGs) and anti-PF4 antibodies. In this study, we quantified the levels of anti-PF4 antibody isotypes and endogenous GAGs together with inflammatory biomarkers in pulmonary embolism (PE) patients to determine whether there is a relationship in between. Identification of this relationship may provide insight to the complex pathophysiology of PE and HIT and may also be useful for development of potential prognostic, diagnostic and therapeutic interventions.Materials and MethodsPlasma samples from PE patients (n: 210) were analyzed for anti-PF4 antibody isotypes and various thrombo-inflammatory cytokines utilizing commercially available biochip array and ELISA methods. The endogenous GAG levels in PE patients? plasma were quantified using a fluorescence quenching method. The collected data analyzed to demonstrate the relationship between various parameters.ResultsThe endogenous GAG levels were increased in the PE group (P?